Temperature dependence of photosynthesis and thylakoid lipid composition in the red snow alga Chlamydomonas cf. nivalis (Chlorophyceae). Issue 2 (7th March 2014) - Lukeš, Martin; Procházková, Lenka; Shmidt, Volha; Nedbalová, Linda; Kaftan, David
Abstract Here, we report an effect of short acclimation to a wide span of temperatures on photosynthetic electron transfer, lipid and fatty acid composition in the snow alga Chlamydomonas cf. nivalis. The growth and oxygen evolution capacity were low at 2 °C yet progressively enhanced at 10 °C and were significantly higher at temperatures from 5 to 15 °C in comparison with the mesophilic control Chlamydomonas reinhardtii. In search of the molecular mechanisms responsible for the adaptation of photosynthesis to low temperatures, we have found unprecedented high rates of QA to QB electron transfer. The thermodynamics of the process revealed the existence of an increased structural flexibility that we explain with the amino acid changes in the D1 protein combined with the physico‐chemical characteristics of the thylakoid membrane composed of > 80% negatively charged phosphatidylglycerol.